Measuring the signaling value of educational degrees: secondary education systems and the internal homogeneity of educational groups - Jan Paul Heisig (Large-scale Assessments in Education, 2018)
[BACKGROUND:] By providing high-quality, internationally comparable data on the cognitive skills of working-age adults, the Programme for the International Assessment of Adult Competencies (PIAAC) offers great potential for illuminating the complex interplay of formal qualifications and skills in shaping labor market attainment as well as social inequalities more broadly. I argue that PIAAC can be used to construct direct, country-level measures of the `skill transparency' or `signaling value' of formal qualifications, that is, of how informative the latter are about a person's actual skills. The primary goal of the analysis is to extend previous work on skills gaps by educational attainment and map cross-national variation in the internal skills homogeneity of educational groups as a second dimension shaping the signaling value of educational degrees. I also explore whether the internal homogeneity of educational groups is related to national (secondary) education systems. [METHODS:] I use a sample of 30,646 20-to-34-year-olds in 21 countries that participated in the first round of PIAAC. The internal homogeneity of educational groups is measured using the residual standard deviation of literacy and numeracy skills after adjusting for sex, age, and foreign-birth/foreign-language status. Residual standard deviations for the different educational groups are subjected to a factor analysis to construct a one-dimensional measure of internal homogeneity for each country. This index of internal homogeneity is then related to education system characteristics in a series of country-level regressions. [RESULTS:] The internal homogeneity of educational groups with respect to literacy and numeracy skills varies considerably across countries and is highly correlated across both skill domains and educational groups. Educational groups tend to be more homogeneous in countries with stronger (ability-related) tracking in secondary education. In addition, there is some evidence that internal homogeneity declines when instructional resources such as computer hardware and lab equipment are distributed more unequally across schools. An unexpected finding is that internal homogeneity is negatively associated with standardization of input (e.g., curricula, textbooks). [CONCLUSIONS:] The signaling value of educational degrees varies substantially across advanced economies, not only in terms of skills gaps among educational groups, but also in terms of their internal homogeneity. Some features of secondary education systems appear to be systematically related to the extent of internal homogeneity. The findings lend empirical support to so far untested assumptions about the relationship between formal qualifications and skills in cross-national research on labor market inequalities.
Keywords: 330; PIAAC; education systems; educational credentials; labor market attainment; signaling; screening; human capital theory